Visualizing Lake Ontario through the Installations of Bonnie Devine and Nicole Clouston - MacGregor, Gwen (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2019)
This article explores the efficacy and physicality of Lake Ontario through its lack of a border vista, a physical feature in much of the rest of the country that contributes to the geographic imaginary of Canada. Within this context, the article discusses two art installations––Battle for the Woodlands (2014-2015) by Bonnie Devine and A Portrait of Lake Ontario (2017) by Nicole Clouston––both of which engage with the integrated, material, and lively watershed of Lake Ontario. “Vital materiality” and decolonial literatures are also engaged with to show how the installations reaffirm the efficacy and physicality of Lake Ontario and the ways in which it stands as a resistant space in relation to the colonial nation-state of Canada with its arbitrary borders.